Pelatihan Penyusunan Dokumen Sertifikasi Halal Bagi UMKM di Kota Batam - Kurniawan, Ded; Setiyanto, Adi Irawan; Darmawan, Arif; Ansori, Muslim; Restu, Fedia; Aprilia, Elin; Widiastuti, Hanifah; Zaenuddin, Muhammad; Wijayanti, Ita; Rasarandi, Farouki Dinda (Politeknik Negeri Batam, 2023)
This service activity has two objectives. First, increasing the understanding of halal certification for MSMEs in Batam City. Second, helping SMEs in Batam City to prepare halal certification documents. This activity is carried out to overcome problems in MSMEs regarding the management of halal certification. This activity is expected to be useful for MSME Managers so that they understand the urgency of halal products, then MSME products are halal certified, and finally as a means of student learning. Based on the results of the assistance, many MSMEs want to take care of halal certification but are still confused about the preparation. This activity contains socialization, training, and mentoring. Assistance is provided to 6 (six) business units.